EVALUATION OF THE USEFULNESS OF SHEAR WAVE ELASTOGRAPHY IN THE DIAGNOSTIC PROCESS FOR NONCANCEROUS SOFT TISSUE MASSES - SATTAR, A; ANJUM, S; MUSHTAQ, S; YOUSAF, J; NASIR, U (Biological and Clinical Sciences Research Journal, 2022)
Current study was carried out to assess efficacy of SWE as an adjunct to sonography in investigating superficial benign lesions. The retrospective study was conducted in Radiology department of Nishtar Medical Hospital from July 2021 to July 2022. The study included 45 patients with 49 lesions. Doppler and grayscale ultrasound and SWE was performed. Conventional ultrasonic features like depth (mm), size (mm), margin (ill defined or well defined), vascularity (present or absent) and echogenicity (isoechoic, anechoic, hyperechoic or hypoechoic) were investigated. Median shear modulus and ultrasonic features were documented. Mean shear modulus for epidermoid, ganglion and lipomatous cyst was 23.6kPa, 5.9kPa and 9.1kPa respectively. Difference between lipomatous tumors, ganglion cysts and epidermoid cysts were significant (P=0.018). Median shear modulus of epidermoid cyst was higher than ganglion cysts and lipomatous tumors. Shear wave elastography is valuable modality for diagnosis of superficial benign soft tissue masses through direct quantitative analysis.